Peculiar properties of the financial state of companies with falling income - P. N. Brusov; T. V. Filatova; A. D. Kashirin; V. L . Kulik (Финансы: теория и практика)
The recent rise in inflation in Europe, caused by the pandemic, the increase in prices for energy resources and the violation of the logistics of energy supplies, has led to a decrease in company income. This makes it relevant to study the financial condition of companies with falling revenues. The purpose of this study is the development of tools for quantifying the impact of falling company incomes is becoming essential for making adequate management decisions. Until recently, such tools in capital structure theory did not exist. Two main theories of the capital cost and capital structure — Brusov — Filatova — Orekhova (BFO) theory and Modigliani — Miller (MM) theory — described companies with constant revenue: the first — for arbitrary age company, the second — for perpetuity companies. Within last couple years both these theories have been generalized for the case of variable revenue. In this paper the peculiar properties of the financial state of companies with falling income are studied within the modern capital cost and capital structure theory — Brusov–Filatova– Orekhova (BFO) theory, generalized for the case of variable revenue. As part of the goal, the tasks are solved to study the behavior of the main financial indicators (the cost of raising capital, the discount rate, the company’s capitalization, the cost of equity, and others), their dependence on debt financing, the age of the company in the face of declining income, which will make it possible to make adequate management decisions and reduce risks for companies.